Colostomy in Hirschsprung disease. - Sbárbaro, Orestes; Benedictti, Juan L (Cirugía del Uruguay, 1984)
Colostomy is more frequently used in the newborn and the suckling baby Hirschsprung disease, performance of this technique is very seldom used in children. There is no unanimous opinion as to the indications of colostomy as the procedure of election prior to the definitive treatment. Those not indicating it propound to perform the definitive entrace procedure.